Salinity significantly affects methane oxidation and methanotrophic community in Inner Mongolia lake sediments - Zhang, Shaohua; Yan, Lei; Cao, Jiahui; Wang, Kexin; Luo, Ying; Hu, Haiyang; Wang, Lixin; Yu, Ruihong; Pan, Baozhu; Yu, Ke; Zhao, Ji; Bao, Zhihua (Frontiers in Microbiology, 2023)
Methanotrophs oxidize methane (CH4), which helps greatly in mitigating greenhouse effect. Increased temperatures due to global climate change can increase wetland or lake salinization, particularly in the regions with cold semiarid climate. Therefore, we collected lake sediment samples from 13 sites in Mongolian Plateau. CH4 oxidation activities of methanotrophs were investigated, and the diversity and abundance of methanotrophs were analyzed using real-time quantitative polymerase chain reaction and high throughput sequencing approach. The results revealed that the diversity of methanotrophic community decreased with increasing salinity, and community structure distribution of methanotrophs was clearly different between the hypersaline sediment samples (HRS; salinity > 0.69%) and hyposaline sediment samples (HOS; salinity < 0.69%). Types II and I methanotrophs were the most dominant in HRS and HOS, respectively. Salinity was significantly positively correlated with relative abundance of Methylosinus and negatively correlated with that of Methylococcus. In addition, CH4 oxidation rate and pmoA gene abundance decreased with increased salinity, and salinity directly and indirectly affected CH4 oxidation rate via regulating the community diversity. Moreover, high salinity decreased both methanotrophs co-occurrence network relationship and number of key methanotrophic species. These results suggested that salinity is a major driver of CH4 oxidation in lake sediments and acts by regulating the diversity of methanotrophic community and interaction among the methanotrophic species.